Perancangan Sistem Informasi Pengolahan Data Morbiditas Rawat Inap Guna Menunjang Tata Kelola Pelaporan Rawat Inap - Fahrudin, Hanif; Abdussalaam, Falaah; Sari, Irda (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Morbidity is a crucial aspect that must be reported regularly, specifically quarterly (RL4a). This study aims to support the governance of inpatient unit reporting, especially in the aspect of morbidity, and make it easier for medical record officers as system users to process morbidity data of inpatient unit patients into a report that is needed quickly, accurately, and efficiently. This research is qualitative, and data is collected using observation techniques. This research's system development method is the waterfall model, which is a consecutive development method analogous to a waterfall that flows across all project stages. Designing an inpatient morbidity data processing system to support inpatient reporting governance is described using a flow map, Context diagram, Data flow diagram, and Entity relationship diagram. Then, it was implemented into the website using Microsoft Visual Studio Code using the Hypertext Preprocessor, Javascript programming language, and supported by MySQL as a data store. This study results in a system that can quickly process the morbidity of inpatient units, make the extensive ten disease reports, and reduce user error. Therefore, the governance of inpatient reporting can run accurately and efficiently.